Disability and Emergency Department Visits: A Path Analysis of the Mediating Effects of Unmet Healthcare Needs and Chronic Diseases - Seungeun Park PhD, MPH, RN; Jae-Hyun Park PhD, MD (Inquiry: The Journal of Health Care Organization, Provision, and Financing, 2023)
Previous studies identified disabilities and unmet healthcare needs, especially those related to primary healthcare, as predictors of ED use. This study examined the relationship between disability, unmet healthcare needs, chronic diseases, and ED visits in South Korea. This study was a cross-sectional study using the Korean Health Panel Survey collected in 2018. A path analysis was used. Our research found a significant association between disability and ED visits mediated by unmet healthcare needs and chronic diseases. Disability had a significant direct effect on unmet healthcare needs (β = .04, P  ≤ .001) and chronic diseases (β = .10, P  ≤ .001). However, there was no mediating effect of unmet healthcare needs between disability and ED visits. While barriers to access to care among people with disabilities are widely acknowledged, this study suggests that interventions or programs to reduce ED visits should consider the unique healthcare needs of people with disabilities.